The Effect of Remuneration of Directors and Commissioners, Enterprise Risk Management on Financial Distress with Firm Life Cycle as Moderation - Indira Salsabila; Hasnawati Hasnawati (CV. Publikasi Indonesia, 2024)
This study aims to determine the effect of Remuneration of Directors and Commissioners, Enterprise Risk Management on Financial Distress with Firm Life Cycle as moderation. This study uses secondary data obtained from the company's financial statements and annual reports. The amount of data in this research population is 150 data from retail companies listed on the Indonesia Stock Exchange (IDX) for the period 2017 - 2022. The analysis technique used in this research is moderated linear regression analysis which is processed using SPSS version 27. The results of this study are enterprise risk management has a negative effect on financial distress, firm life cycle strengthens the relationship between remuneration of directors and commissioners on financial distress, remuneration of directors and commissioners has no effect on reducing the level of financial distress, firm life cycle has no effect on the relationship between enterprise risk management and financial distress.